Epidemiology of malocclusions in primary dentition and associated factors (Revista da Faculdade de Odontologia - UPF, 2017)
Objective: this study aimed to evaluate malocclusion occurrence in children with complete primary dentition, describing the most frequent one and verifying potential associations with demographic, socioeconomic, and behavioral variables. Subjects and method: 502children with complete primary dentition from primary schools in the city of Pelotas, RS, Brazil, were examined. Data was collected based on questionnaires distributed to the mothers, as well as on physical examinations of the oral cavity. The children with malocclusion presented at least one of the following changes: anterior open bite, deep overbite, posterior crossbite, and overjet. Chi-square tests for heterogeneity and linear trend were used to verify associations with demographic, socioeconomic, and behavioral variables. Results: the occurrence of malocclusions in the population studied was 67.5%. From them, 33.6% presented anterior open bite, 22.3% presented deep overbite, 9.8% presented posterior crossbite, and overjet was present in 1.8%.The most frequent malocclusion was anterior open bite, which was directly associated with the use of pacifier (p